Associations Between Lifetime Histories of Iron Deficiency, Anxiety, Depression and Multiple Pain Conditions: An Observational Study Using a Large-Scale National Database - Champion D; Bui M; Aouad P; Teng A; Walters AS; Karroum EG; Tan AC; Yang Z; Joyce E; Jaaniste T (Journal of Pain Research)
David Champion,1,2 Minh Bui,3 Phillip Aouad,2,* Arthur Teng,1,4,* Arthur S Walters,5,* Elias Georges Karroum,6,* Aidan Christopher Tan,1,2,* Zijing Yang,7,* Emily Joyce,8,* Tiina Jaaniste1,2 1School of Clinical Medicine, University of New South Wales, UNSW, Sydney, NSW, 2052, Australia; 2Department of Pain Medicine, Sydney Children`s Hospital, Randwick, NSW, 2031, Australia; 3Centre for Epidemiology and Biostatistics in the School of Population and Global Health, The University of Melbourne, Parkville, VIC, 3010, Australia; 4Department of Sleep Medicine, Sydney Children`s Hospital, Randwick, NSW, 2031, Australia; 5Department of Neurology, Sleep Division, Vanderbilt University School of Medicine, Nashville, TN, 37232, USA; 6Department of Neurology, University of Virginia School of Medicine, Charlottesville, VA, 22903, USA; 7Department of Inflammation Biology, School of Immunology and Microbial Sciences, Centre for Rheumatic Diseases, King’s College, London Strand, London, WC2R 2LS, UK; 8Faculty of Science, University of Sydney, Sydney, NSW, 2006, Australia*These authors contributed equally to this workCorrespondence: David Champion, Department of Pain Medicine, Bright Alliance Building, Level 7, Sydney Children`s Hospital, Randwick, NSW, 2031, Australia, Tel +61 410405020, Email gdavidchampion@gmail.comPurpose: Our aims were to investigate in adults, as we have shown in three paediatric samples, associations between a history of iron deficiency (whenever acquired and treated) and history (> 3 months) of primary, overlapping and multisite chronic pain conditions, and to investigate associations between history of iron deficiency, anxiety, and depression.Participants and Methods: We recruited adult twins and their families from the Australian Twin Registry database. Responders addressed questionnaires about lifetime history of iron deficiency > 3 months, diagnosed and treated by a physician, and a history > 3 months of listed pain conditions, anxiety and depression. The emphasis was on life history, not current status, of each of these conditions and such questions were the only practical method. Logistic regression, using generalized estimating equation to account for correlations within twin families, was employed to assess relationships between iron deficiency and pain conditions and the psychological conditions.Results: Of the 1519 adult responders, 1326 addressed the criteria for iron deficiency, and the prevalence was 38.7% in females and 2.4% in males. Iron deficiency as statistical predictor was significantly associated with migraine (Odds ratio (OR)=1.70, p=0.001), headache (OR=1.37, p=0.03), recurrent abdominal pain (OR=1.97, p< 0.001), dysmenorrhea (OR=2.18, p< 0.001), anxiety (OR=1.88, p< 0.001) and depression (OR=2.06, p< 0.001). Iron deficiency, anxiety and depression, as statistical predictors, were univariately and multivariately associated with the number of pain conditions (all p< 0.05).Conclusion: A history of iron deficiency in a community sample of adults was associated with most individual, primary, overlapping and multisite pain conditions tested, and multivariately associated with the number of pain conditions, and with anxiety and depression. We hypothesize, consistent with these results, that previous or current iron deficiency, even when treated, influences pain sensitivity and multiplicity directly and through known effects on anxiety and depression.Keywords: iron deficiency, primary pain conditions, overlapping pain conditions, multisite pain conditions, anxiety, depression, twin family survey, association analyses